IMPROVING THE MANAGEMENT OF WASTEWATER REUSE TO IRRIGATE LANDSCAPE - Elshymaa Solima ELdeeb; Mahmoiud Hegazi; Osama Bedair (Arab Universities Journal of Agricultural Sciences, 2020)
This study aimed to measure the effect of treated wastewater on the performance of pressure irrigation network components and compare it with domestic water. The experiments were conducted in Eastown and Lake View sites in the Fifth Settlement - New Cairo, at N = 30° 01' 14.4", E = 31° 51' 60.9" and N = 30° 02' 22", E = 31° 44' 31.3", respectively, and the experiments were done in (2019). The area under investigation was 155 m², divided into three plots (5×5 m) for spray irrigation, there areas were planted with turf grass (passpalm 10), and three plots (5×2 m) for drip irrigation, there areas were planted with shrubs (Lantana camara nana) and trees (Calistemon viminalis). By irrigation with two types of water: treated wastewater and domestic water with the use of two types of filters in the Lake View site (a screen filter and a sandy filter) and the use of one type of filters in the Eastown site, which is screen filter. The washing process was carried out manually and automatically. The results showed significant effects on the components of the network and on the general appearance of the vitality and shape of the cultivated surfaces. The most important results obtained were: • Emission uniformity for drip system in Lake View site, was higher when using automatic operation with treated wastewater by (5 and 6%) for on-line dripper and built-in dripper, respectively, than manual operation, while, in Eastown site emission uniformity was higher when using automatic operation with treated wastewater by (2.3 and 4.9 %) for on-line dripper and built-in dripper, respectively, than manual operation. • Distribution uniformity for spray system was higher when using automatic operation with treated wastewater by (5 and 5.1%) in Lake View site and Eastown site, respectively, than manual operation. • Clogging ratio in Lake View site by using manual operation with treated wastewater was (40 and 48%) for on-line dripper and built-in dripper, respectively. Clogging ratio using automatic operation was (20 and 25%) for on-line dripper and built-in dripper, respectively, while, in Eastown site by using manual operation with treated wastewater was (34.5 and 44.7%) for on-line dripper and built-in dripper, respectively, and by using automatic operation was (18.75 and 22%) for online dripper and built-in dripper, respectively. It was higher with manual operation than automatic operation and higher with treated wastewater than domestic water. • The concentration of total suspended solids was less by (93.6 and 97.9%) with manual and automatic operations, respectively in Lake View site, while, it was less by (50 and 60%) with manual and automatic operations, respectively, in Eastown site. • The turf quality index (color, density, ground cover) gave the highest degree when using treated wastewater with automatic operation, which is due to the nutrients in treated wastewater. • It is preferable to use sand filters before the mesh filters with treated wastewater to reduce the percentage of clogging with impurities instead of using only mesh filters.